Rekonstruksi Hukum Zakat Profesi dalam Perspektif Fikih Kontemporer - Deviyana Khoirotul Iswiyah (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
The shift in the structure of modern society's economy from an agrarian base to a service- and expertise-based one has given rise to new forms of income, namely salaries, wages, and professional honorariums, which are not explicitly regulated in classical zakat fiqh. This phenomenon has generated the discourse on professional zakat (zakat profesi) as one of the central issues in contemporary fiqh muamalah. This article aims to analyze the legal basis, the methods for determining nisab and haul, and the map of scholarly disagreement (ikhtilaf) regarding professional zakat, while also examining its relevance to the objective of social justice in Islam. This study employs a qualitative method with a normative-juridical approach through library research, examining the Qur'an, hadith, legal maxims (qawa'id fiqhiyyah), fatwas of religious institutions, and journal articles published within the last five years. The findings show that the majority of contemporary scholars, including Yusuf al-Qardhawi, obligate professional zakat based on the general implication of zakat verses and the method of analogical reasoning (qiyas), likening it to the zakat on gold and silver in terms of nisab (equivalent to 85 grams of gold, at a rate of 2.5%) or to agricultural zakat in terms of the timing of payment. However, some scholars, particularly those adhering to the principle of tauqifiyyah in worship, reject the obligation of professional zakat as a distinct category because it lacks explicit textual basis. This disagreement reflects the methodological tension between textual and contextual approaches in legal reasoning (istinbath al-ahkam), while also demonstrating the flexibility of Islamic fiqh in responding to socio-economic dynamics without abandoning the fundamental principles of sharia. Keywords: Professional Zakat, Contemporary Fiqh, Qiyas, Nisab And Haul, Scholarly Disagreement.